Validity of PowerTap P1 pedals during laboratory-based cycling time trial performance - Whittle, C.; Smith, N.; Jobson, S. A. (Sports, 2018)
The use of mobile power measuring devices has become widespread within cycling, with a number of manufacturers now offering power measuring pedals. This study aimed to investigate the validity of PowerTap P1 pedals by comparing them with the previously validated Wattbike ergometer. Ten trained cyclists performed three simulated 10-mile (16-km) time trials on a Wattbike, while using PowerTap P1 pedals. There were no statistically significant differences (p > 0.05) between PowerTap P1 pedals and a Wattbike for maximum, minimum, and mean power output, or for maximum, minimum, and mean cadence. There were good to excellent levels of agreement between the PowerTap P1 pedals and Wattbike (ICC > 0.8) for all measured variables except minimum cadence (ICC = 0.619). This suggests that PowerTap P1 pedals provide a valid measurement of power output.